Respuesta :

Change the sign on the first one, making it -2x -y = 1

Then combine the terms you have,
-2x-y=1
and
6x+y=-21
And this will give you
4x=20

Then solve that equation for x by dividing both sides by 4, giving you x=4

Then plug 5 into x’s place in either of the original equations.

This is if you use the first equation
2(5)+y=-1
Solve for y by simplifying
10+y=-1
Then subtract 10 from both sides
y=-11.

The final answer is x=5 and y=-11
Solve for y
2x+y=-1
y=-2x-1
Sub y= -2x-1 into an equation and solve for x
6x-2x-1=-21
4x-1=-21
4x=-20
x=-5
Sub -5 for x in either equation
2(-5)+y=-1
-10 + y=-1
y=9
Check answer by substituting both solutions
6(-5)+9=-21
-30+9=-21
-21=-21

2(-5)+9=-1
-10+9=-1
-1=-1

x=-5, y=9